Assassination classroom. 3, Time for a transfer student - Matsui, Yūsei, 1981-; Turnage, Bryant (Shonen Jump advanced., 2015)
"The latest addition to the misfit students of Class 3-E is a Norwegian robot specially designed to assassinate their teacher-- but sadly lacking in social skills. Nothing Koro Sensei can't cure with a little super-fast tentacle work! When playboy Maehara gets dissed by a girl for being in Class 3-E, revenge is clearly warranted and Koro Sensei can help with that too! Then Irina, the English language teacher/sexy assassin, gets a visit from her murder mentor. Plus, secrets of Koro Sensei's mysterious past revealed!"--P. [4] of cover.